Character Education Of TNI in Facing Globalization Challenges: (Character Education Study at the Mental Development Center Of TNI) - Ghazalie, Ghazalie (Advances in Social Sciences Research Journal, 2020)
This study discusses the concept of TNI character education not yet ready to face the challenges of globalization. This conclusion is based on the current mental condition of the TNI which is still evidenced by the completion of the soldiers. In addition, differences were also found in TNI character education, namely in the aspects of the organization, human resources, curriculum, methods, and facilities. The weakness of character education in some of these aspects needs to be modernized, because TNI character education has a significant effect on the formation of the mindset, attitudes and behavior of soldiers, so improving the character of a solid soldier education will produce good soldier attitudes and behavior. This study examines character education in the struggle of globalization by using qualitative research, giving meaning behind data, facts, phenomena related to using historical, sociological, and Islamic education. Classical background is used to reveal the educational background of the TNI character. Sociological relations are used to see the relationship and the relationship between the education of TNI characters and phenomena and influencing factors. The value of Islamic education is used to see Islamic values ​​transformed in the character education of the TNI. The main data source (primary) in this study is data obtained from field research (field research) through interviews, observation and documentation. Secondary data sources are books published with discussion, authoritative articles written by experts.